UPDATE OF CLIMATOLOGICAL NORMAL AND KÖPPEN CLIMATE CLASSIFICATION FOR THE MUNICIPALITY OF BOTUCATU-SP - Franco, José Rafael [UNESP] (2023)
The climate has been observed for thousands of years throughout human development, its knowledge is fundamental for agricultural practices. Climate classification is a difficult task due to the period of data required for its identification, at least 30 years of recorded measurements, as recommended by the World Meteorological Organization. The objective of this research is to identify the climatic normals of the elements of the climate and to update the climatic classification of the municipality of Botucatu-SP, using the method proposed by Köppen (1918) and adapted by Setzer (1966). The elements analyzed were rainfall, relative humidity and average air temperature. Daily data from the local meteorological station were used, from 1991 to 2020. The climatological normals were identified with an average air temperature of 21.34°C, an average relative humidity of 70% and an average annual precipitation of 1500 mm, with average occurrence of precipitation in 107 days of the year. Analyzing the data of the new climatic normal according to Köppen, the climate of Botucatu-SP was identified with Aw, unlike the previous classifications, with hot and humid summers (higher temperature and precipitation) and cold and dry winters (low temperature and precipitation).